X-Ray Cavity Dynamics and Their Role in the Gas Precipitation in Planck Sunyaev–Zeldovich (SZ) Selected Clusters - V. Olivares; Y. Su; W. Forman; M. Gaspari; F. Andrade-Santos; P. Salome; P. Nulsen; A. Edge; F. Combes; C. Jones (The Astrophysical Journal, 2023)
We study active galactic nucleus (AGN) feedback in nearby ( z < 0.35) galaxy clusters from the Planck Sunyaev–Zeldovich sample using Chandra observations. This nearly unbiased mass-selected sample includes both relaxed and disturbed clusters and may reflect the entire AGN feedback cycle. We find that relaxed clusters better follow the one-to-one relation of cavity power versus cooling luminosity, while disturbed clusters display higher cavity power for a given cooling luminosity, likely reflecting a difference in cooling and feedback efficiency. Disturbed clusters are also found to contain asymmetric cavities when compared to relaxed clusters, hinting toward the influence of the intracluster medium (ICM) “weather” on the distribution and morphology of the cavities. Disturbed clusters do not have fewer cavities than relaxed clusters, suggesting that cavities are difficult to disrupt. Thus, multiple cavities are a natural outcome of recurrent AGN outbursts. As in previous studies, we confirm that clusters with short central cooling times, t _cool , and low central entropy values, K _0 , contain warm ionized (10,000 K) or cold molecular (<100 K) gas, consistent with ICM cooling and a precipitation/chaotic cold accretion scenario. We analyzed archival Multi-Unit Spectroscopic Explorer observations that are available for 18 clusters. In 11/18 of the cases, the projected optical line emission filaments appear to be located beneath or around the cavity rims, indicating that AGN feedback plays an important role in forming the warm filaments by likely enhancing turbulence or uplift. In the remaining cases (7/18), the clusters either lack cavities or their association of filaments with cavities is vague, suggesting alternative turbulence-driven mechanisms (sloshing/mergers) or physical time delays are involved.